The relationships between agricultural, manufacturing and services sectors with poverty rate in Malaysia / Siti Zuraida Ibrahim (Faculty of Business and Management, 2006)
This project paper is to identify the relationship between growth of three sectors in Malaysia, namely agriculture, manufacturing and services sectors and the incidence of poverty. These three independent variables are the main sectors that contribute to the nation's growth. The dependent variable is incidence of poverty rate and the dependent variable are the output produced by the three sectors as proxy to growth in the country. The study focuses on the annual data collected from 1975 until 2005. This research used the Statistical Package for Social Science (SPSS) by using the method of Multiple Linear Regression Analysis to find out the relationship between dependent variable and independent variables. From the findings, it is concluded that growth attributed by agriculture sector has a positive relationship with incidence of poverty, whereas for service sector and manufacturing sector, they have negative relationships with the incidence of poverty. Based on the T-statistic values, only the outputs from services and agriculture have significant relationships with the dependent variable, while the manufacturing sector does not have a significant relationship with the incidence of poverty in Malaysia.